Hematologies The Political Life of Blood in India - Copeman, Jacob (Cornell University Press, 2019)
In this ground-breaking account of the political economy and cultural meaning of blood in contemporary India, Jacob Copeman and Dwaipayan Banerjee examine how the giving and receiving of blood has shaped social and political life. Hematologies traces how the substance congeals political ideologies, biomedical rationalities, and activist practices.Using examples from anti-colonial appeals to blood sacrifice as a political philosophy to contemporary portraits of political leaders drawn with blood, from the use of the substance by Bhopali children as a material of activism to biomedical anxieties and aporias about the excess and lack of donation, Hematologies broaches how political life in India has been shaped through the use of blood and through contestations about blood. As such, the authors offer new entryways into thinking about politics and economy through a "bloodscape of difference": different sovereignties; different proportionalities; and different temporalities. These entryways allow the authors to explore the relation between blood's utopic flows and political clottings as it moves through time and space, conjuring new kinds of social collectivities while reanimating older forms, and always in a reflexive relation to norms that guide its proper flow.